THE LEVEL OF KNOWLEDGE AND ATTITUDE OF TRADITIONAL FISHERMEN IN GUAERIA TOWARDS THE RISK OF EAR BAROTRAUMA - Nurhalisah; Upik En Masrika, Nur; Fera The; Dewi, Nurmala (Jurnal Farmasi Sains dan Praktis, 2026)
Traditional fishermen in remote coastal villages often use simple diving methods with unmonitored dive depth and duration, increasing their risk of ear barotrauma, particularly due to a lack of knowledge and formal training. This study aimed to assess the level of knowledge and attitudes toward ear barotrauma risk among traditional fishermen in Guaeria Village, Jailolo District, West Halmahera Regency, North Maluku Province. This observational study used a cross-sectional design with a total sampling technique, involving all 41 traditional fishermen in the village. Data were collected through structured interviews using a validated questionnaire and analyzed descriptively using SPSS. The results showed that most respondents were aged over 40 years (68.3%), male (100%), had worked for more than 1 year (78%), dove less than 4 days per week (61%), had a normal body mass index (73.2%), and dove for more than 30 minutes per session (70.7%). All respondents (100%) reported a history of barotrauma, with symptoms including ear pain (90.2%), dizziness (90.2%), tinnitus (73.2%), nosebleeds (58.5%), hearing loss (46.3%), and ear bleeding (36.6%). Most fishermen had insufficient knowledge (78.1%) but a sufficient attitude (68.3%) regarding barotrauma risk. In conclusion, traditional fishermen in Guaeria Village show a high prevalence of ear barotrauma symptoms; although their attitude toward barotrauma risk is fairly good, their knowledge remains insufficient, likely due to limited access to information and formal education on diving health risks.